Implementation of a standardised perioperative nutrition care pathway in upper gastrointestinal cancer surgery: A multisite pilot study. Issue 2 (18th May 2022) - Deftereos, Irene; Hitch, Danielle; Butzkueven, Sally; Carter, Vanessa; Arslan, Janan; Fetterplace, Kate; Fox, Kate; Ottaway, Aurora; Pierce, Kathryn; Steer, Belinda; Varghese, Jessie; Kiss, Nicole; et al.
Abstract: Background: Perioperative nutrition support is recommended for patients undergoing upper gastrointestinal (UGI) cancer surgery; however, limited evidence exists regarding implementation of a nutrition care pathway in clinical practice. The aims of this pilot study were to determine whether implementation of a standardised perioperative nutrition pathway for patients undergoing UGI cancer surgery improves access to dietetics care, as well as to evaluate study feasibility, fidelity, resource requirements and effect on clinical outcomes. Methods: Patients with newly diagnosed UGI cancer from four major metropolitan hospitals in Melbourne, planned for curative intent surgery, were included in the prospective pilot study ( n = 35), with historical controls ( n = 35) as standard care. Outcomes were dietetics care (dietetics contacts) nutritional status, hand grip strength, weight change, preoperative hospital admissions, complications and length of stay, recruitment feasibility, fidelity and adherence, and resource requirements. Continuous data were analysed using independent samples t test accounting for unequal variances or a Mann–Whitney U test. Dichotomous data were analysed using Fisher's exact test. Results: The percentage of participants receiving preoperative dietetic intervention increased from 55% to 100% ( p < 0.001). Mean ± SD dietetics contacts increased from 2.2 ± 3.7 to 5.9 ± 3.9 ( p < 0.001). Non‐statistically significant decreases in preoperative nutrition‐related hospital admissions, and surgical complications were demonstrated in patients who underwent neoadjuvant therapy. Recruitment rate was 81%, and adherence to the nutrition pathway was high (> 70% for all stages of the pathway). The mean ± SD estimated resource requirement for the preoperative period was 3.7 ± 2.8 h per patient. Conclusions: Implementation of this standardised nutrition pathway resulted in improved access to dietetics care. Recruitment feasibility and high fidelity to the intervention suggest that a larger study would be viable. Key points: This was a multisite pilot study investigating the implementation of a standardised perioperative nutrition pathway for patients undergoing upper gastrointestinal cancer surgery compared to standard care. Thirty‐five patients were included in the study and were compared with 35 historical controls. The percentage of participants receiving preoperative dietetic intervention increased from 55% to 100% ( p < 0.001). Mean ± SD dietetics contacts increased from 2.2 ± 3.7 to 5.9 ± 3.9 ( p < 0.001). The recruitment rate was 81%, and adherence to the nutrition pathway was > 70% for all stages of the pathway. Larger prospective studies are required to investigate optimal standardised methods of nutrition support in this patient group. This pilot study demonstrated that a larger trial would be feasible to implement. Abstract : Screening and assessment stage of the nutrition care pathway utilised in this study.